Equity valuation using accounting numbers : an assessment of earnings value relevance - Marques, Diogo Filipe de Abreu (2018)
Asset valuation is not a straightforward task, whether we are trying to value an entire firm or its equity, assumptions are required, and in some circumstances they are not more than just an educated guess. Equity valuation has been more used and criticized than ever, with the examples from Enron, Comcast and recently Facebook reminding us that market prices should not be taken as absolute. Notwithstanding, the recent openness for seed, venture and public capital raises, reinforces the positive outlook on the both private and public equity markets. Consequently, equity valuation arises as necessary tool to assess current and potential value. Therefore, the purpose of this study is to assess if fundamentals drive equity value, namely earnings, aiming the answer the research question: “Do earnings determine market prices?”. This is done through the application of well-known equity valuation models, such as the dividend discount model, residual income valuation model, price to forward earnings and price to book value multiples to a large sample of U.S. firms in order to assess which model performs the best in determining market prices. Additionally a small sample (two firms) is chosen to exemplify the connection between the extent to which earnings determine market prices and the models’ value estimates errors. Hence, through the analysis of the results from the previous methods, it was possible to assess that firms in which earnings have a higher/lower explanatory power yield lower/higher errors in model pricing using earnings as the value driver.